THE RELATIONSHIP BETWEEN AUDIT COMMITTEE AND FINANCIAL REPORTING QUALITY: APPLIED TO COMMERCIAL COMPANIES IN IRAQ (World Economics and Finance Bulletin, 2023)
This study investigates the strength of the relationship between the audit committee and the quality of financial reports for Iraqi commercial companies. For this purpose, purposive sampling was used to collect data from 50 Iraqi commercial companies. The results demonstrate that all dimensions of the audit committee affect the dimensions of quality of the financial reports, which are timeliness, relevance, faithful representation, comparability and understandability